Exercise Inhibits NLRP3 Inflammasome Activation in Obese Mice via the Anti-Inflammatory Effect of Meteorin-like - Javaid, Hafiz Muhammad Ahmad; Sahar, Namood E; ZhuGe, De-Li; Huh, Joo Young (Cells (Basel, Switzerland), 2021)
Obesity is associated with chronic low-grade inflammation. The benefits of exercise are partly attributed to its anti-inflammatory effect, but whether exercise can regulate NLRP3 inflammasome activation in obese adipose tissue remains unknown. Meteorin-like (METRNL), a recently discovered myokine, has been implicated in mediating the effect of exercise on metabolism. Herein, we examined the effect of exercise and METRNL on NLRP3 inflammasome activation. High-fat diet (HFD)-induced obese mice were subjected to treadmill exercise for 8 weeks. A subgroup of HFD mice was switched to normal chow with the exercise intervention. Exercise and diet attenuated weight gain, fat accumulation, and insulin resistance in obese mice. In addition, exercise downregulated gene and protein levels of inflammasome markers, including NLRP3 and caspase-1, in adipose tissue. In isolated bone marrow-derived macrophages, activation of NLRP3 inflammasome was suppressed in the exercise group, as confirmed by the downregulation of IL-1β and IL-18. Exercise significantly enhanced the expression of METRNL in various muscle depots, and further in vitro analysis revealed that recombinant METRNL treatment inhibited IL-1β secretion in macrophages. In conclusion, exercise exerts its anti-inflammatory action by suppressing adipose tissue NLRP3 inflammasome, and this is, in part, associated with METRNL induction in muscle and its anti-inflammatory effects in macrophages.